Executive green investment vision, stakeholders’ green innovation concerns and enterprise green innovation performance - Wan, Xiaole; Wang, Yuxuan; Qiu, Lulian; Zhang, Kuncheng; Zuo, Jing (Frontiers in Environmental Science, 2022)
During the 14th Five Year Plan period, the green transformation of China's economic growth mode has become the top priority under the carbon peak and carbon neutrality goal. As an important focus of green transformation and development, manufacturing enterprises need to carry out green innovation to cope with the dual pressure of resource and environmental constraints and supply side structural contradictions. Based on the perspective of business ecosystem theory, this study uses fsQCA method to analyze the A-share listed manufacturing enterprise clusters in China's Yangtze River Delta economic belt and the middle reaches of the Yellow River economic belt. The research found that: a) Manufacturing enterprises engaged in green innovation has the characteristics of multi causality and concurrence, and there are mainly four driving paths of high performance level. b) The vision of management and investment is the core supporting factor of green innovation performance. The business ecosystem structure, which combines environmental supervision and competitors' green innovation concerns, is the core driving structure of enterprise green innovation. c) Compared with the academic experience of senior executives, the driving effect of environmental investment plays a greater role in improving the level of innovation performance. The innovation of this study is to introduce the green investment vision of managers and the green innovation concerns of stakeholders into the research framework of green innovation driving paths of manufacturing enterprises, explore different green innovation paths across case sets, and discuss the heterogeneity of the impact of each path on the level of green innovation performance, providing a practical plan of green innovation for managers of manufacturing enterprises, and help them understand which business ecosystem elements can promote efficient green innovation.